Faktor-faktor Pendorong Keniatan Pekerja Lansia untuk Melanjutkan Bekerja - Jati Waskito (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2014)
This study aims to conceptualize the notion of “older worker” intention to continue paid working and to validate a scale of measuring the impact of work related factors on older worker’ intentions to continue in employment. This study uses a cross-sectional, survey-based, self report strategy to gather data. The findings the importance of working, the individuals interest outside works, management and organizational factors, work flexibility, and work attachment are the important things that can influence the older worker to continue paid working